2020
DOI: 10.1097/md.0000000000018727
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the laboratory indexes and risk factors in 189 cases of severe fever with thrombocytopenia syndrome

Abstract: The current study aimed to analyze the clinical characteristics of severe fever with thrombocytopenia syndrome (SFTS) and to explore the risk factors of critical patients. From 2016 to 2018, we collected the hospitalized diagnosed cases with SFTS in Jinan infectious disease hospital of Shandong University and analyzed by the descriptive epidemiological method. According to the prognosis, they were divided into general group and severe group. The epidemiological characteristics, clinical features, and laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
4
18
2
Order By: Relevance
“…Huang et al [19] demonstrated the potential existence of infective virus particles in the mucosa and secretions of patients who may cause asymptomatic infection. The majority of the tickto-person transmission infection group were elderly farmers, a nding similar to many other studies [20].…”
Section: Discussionsupporting
confidence: 88%
“…Huang et al [19] demonstrated the potential existence of infective virus particles in the mucosa and secretions of patients who may cause asymptomatic infection. The majority of the tickto-person transmission infection group were elderly farmers, a nding similar to many other studies [20].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the LDH of patients with neurological complications reached the peak at the multiple organ dysfunction period and return to normal at decubation, while the difference in LDH in the other group was mild ( Figure 2 ). Similar differences can be seen in levels CK, AST, ALP, and GGT ( Figure 3 ), and all of these indicators are risk factors associated with the severity of SFTS [ 30 ]. Contrarily, we found that CRP, which is commonly seen in acute infections or trauma, increased gradually and reached a peak at decubation in the neurologic complications group ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 57%
“…To identify poor prognostic factors, the baseline clinical and laboratory parameters, treatment, and outcomes, including complications of secondary infections, were compared between the fatal and nonfatal groups. The previously reported poor prognostic factors [ 4 , 5 , 6 , 8 , 9 ] were compared between the CS-treated and non-CS-treated groups. The propensity score (PS) was estimated to predict the probability of receiving CS treatment in each patient, using the following key variables: age, mental status changes, and levels of platelet, blood urea nitrogen (BUN), and prothrombin time-international normalized ratio (PT-INR).…”
Section: Methodsmentioning
confidence: 99%
“…The poor prognostic backgrounds for SFTS include advanced age, male sex [ 6 ], and underlying diseases, such as malignancies, diabetes mellitus, chronic viral hepatitis, and chronic obstructive pulmonary disease [ 5 , 7 ]. In addition, patients with central nervous system manifestations [ 4 , 8 ], high levels of alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and creatine kinase (CK) [ 8 ], renal dysfunction [ 9 ], coagulopathy, high level viremia, and hypercytokinemia were reported to show poor prognosis [ 10 ]. To date, no standardized treatment protocol for SFTS has been established.…”
Section: Introductionmentioning
confidence: 99%